2009
DOI: 10.1080/02188790903312706
|View full text |Cite
|
Sign up to set email alerts
|

“My name is Money”: name choices and global identifications at a South-Chinese university

Abstract: Recent communicative language teaching reforms in China have focused on the creative use of English in classroom activities. In response to these reforms, many students have chosen to use English names in classroom, online, and professional contexts, particularly with foreign teachers. Based at a university closely linked to national teaching reforms, this article examines the reasons why university students in China select their English names, and the roles foreign and Chinese teachers play in these choices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Other researchers have found that, while English teachers may be influential in decisions to adopt English names, Chinese speakers are often active and content in the decision to do so. Some students have been found to use English names due to feeling their Chinese names would be too hard for non-Chinese speakers to pronounce (Ghosh andWang, 2003, Gilks, 2014;McPherron, 2009), while others have thought it would reduce the psychological distance between non-Chinese teachers and themselves (Sercombe et al, 2014). Li et al (2007) reported on Chinese-speaking students happily using English names because they made classroom interaction less troublesome, while others enjoyed the feeling of a fresh start involved in taking a new name.…”
Section: The Use Of English Names By Chinese Speakersmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have found that, while English teachers may be influential in decisions to adopt English names, Chinese speakers are often active and content in the decision to do so. Some students have been found to use English names due to feeling their Chinese names would be too hard for non-Chinese speakers to pronounce (Ghosh andWang, 2003, Gilks, 2014;McPherron, 2009), while others have thought it would reduce the psychological distance between non-Chinese teachers and themselves (Sercombe et al, 2014). Li et al (2007) reported on Chinese-speaking students happily using English names because they made classroom interaction less troublesome, while others enjoyed the feeling of a fresh start involved in taking a new name.…”
Section: The Use Of English Names By Chinese Speakersmentioning
confidence: 99%
“…When selecting them, Chinese speakers can make choices that surprise non-Chinese people, including teachers and classmates. In both academic and non-academic discussions of the topic, the apparent oddness of some choices is often highlighted, with the names Medusa (Lee, 2001), Money (McPherron, 2009), Dragon (Henry, 2012), and Ocean (Gilks, 2014) being used in titles of academic articles to emphasise this point. Gilks (2014) explicitly set forth in his study to answer the question "Why do Chinese students make such inappropriate English name choices for themselves?"…”
Section: The Selection Of English Names By Chinese Speakersmentioning
confidence: 99%
“…Despite this reality, English remains an important part of CSU graduates’ professional identity with all interviewees and a large majority of survey participants stating an interest in maintaining their English proficiency and seeking places to use English. Further, similar to the university students’ English name choices discussed in McPherron (), all interviewees had chosen and used an English name in their professional lives because the use of an English name helped to project an English identity even when English was not used in daily tasks.…”
Section: Discussionmentioning
confidence: 99%
“…It has been repeatedly pointed out in the literature that Chinese people tend to like unique English names, including names that are common nouns, such as Butterfly McPherron (2009) noted that mainland Chinese English names may be quite unusual (i.e., not typically American or British), but many of his respondents said that they would change their name if they went abroad.…”
Section: The Nature Of the Namesmentioning
confidence: 99%